The Analysis of The Speech Style Used By Steve Harvey's Talk Show in The Episode “Inspiring Young Man Brings Steve Harvey To Tears” - Diana Angela Bria; Heribertus Binawan (Tarbiatuna: Journal of Islamic Education Studies, 2024)
The purpose of this research is to analyze the speech style used by Steve Harvey in the episode "Inspiring Young Man Brings Steve Harvey to Tears". On Steve Harvey’s official YouTube page called The Steve TV Show, the episode recorded 575,739 views and episodes uploaded on March 24, 2024. The Steve Harvey Show is a television show. This research aims to identify and categorize the various speech styles used by Steve Harvey (Host) and Walter Carr (guest) in the episode, as well as to understand the context and function of each style. The method used in this research is qualitative descriptive analysis for data collection. Data collected from analyzed video and transcripts of talk show episodes were analyzed and then classified based on the theory of Joos Martin (1962), which divides speech style into five levels, namely: frozen style, formal style, consultative style, informal style, and intimate style. Based on Joos Martin’s theory, Steve Harvey and Walter Carr preferred Consultative Speech Style at 84,62%, Casual Speech Style at 7,69%, Formal Speech Style at 15,38%, Intimate Speech Style at 0%, Frozen Speech Style at 0% emerging during intense emotional moments at and the guest. These findings explain how speech style preferences influence interaction and emotional resonance in talk-show situations.